Peran Perceived Usefulness dan Perceived Risk sebagai Variabel Pemediasi pada Pengaruh Perceived Ease of Use dan e-WOM Negatif terhadap Niat Pembelian Para Pengguna Aplikasi Layanan Kesehatan Halodoc - Wakhida, Ursila Imro'atu; Sanaji, Sanaji (Jurnal Ilmu Manajemen, 2020)
Competition in the business world today is increasingly fierce in the era of globalization. Information technology can shift the way of practice and change the way of thinking in the business world. The rapid development of technology makes the economy also increasingly developing. One of them is the innovation in the field of online health services. This study aims to examine the effect of perceived ease of use and negative EWOM on purchase intentions with perceived usefulness and perceived risk as mediating variables in Halodoc health service application users in East Java. This study uses 200 samples with non-probability sampling techniques and the method used is a judgmental sampling. The data collection method is done by distributing questionnaires online. The data analysis technique used in this study is the path analysis technique. Based on the results of research conducted, it was found that perceived ease of use has a positive effect on purchase intentions with perceived usefulness as a mediating variable, and negative EWOM has no effect on purchase intentions because perceived risk does not mediate between these relationships in Halodoc health service applications. Based on these results, it is recommended that Halodoc health service application makers pay attention to the ease of use of the application and the benefits that can be felt by consumers and prospective consumers when using the application so that a positive EWOM is formed to reduce the risks that exist in the application and have an impact on purchase intentions towards health services in the application.